Hasil Analisis Teknik Data Mining dengan Metode Naive Bayes untuk Mendiagnosa Penyakit Kanker Payudara - Elma Tiana; Sri Wahyuni (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
Breast cancer or Mammae Carsinoma is an uncontrolled cell growth in the milk-producing glands (lobular), the gland tract from the lobular to the Breast nipple (ductus), and the breast support tissues that surround the lobular, ductus, vessels Blood and limfe vessels, but does not include breast skin. Research begins by conducting a preprocessing stage, to eliminate missing values. After that the process is imputasi to remove missing values. It then performed a feature selection to see which attribute had a major impact on the data. The last stage is classification with two methods, namely Naïve Bayes. At the end of the study, the method is best to classify the recurrence data of breast cancer patients.